No peace to keep: Darfur in perspective - Lee J. M. Seymour (Stiftung Wissenschaft und Politik (SWP), 2007)
April and May witnessed intensified diplomatic activity around the conflict in Darfur. This culminated in the US government's announcement of new sanctions on the government of Sudan and a push at the Security Council for targeted sanctions and expansion of the existing arms embargo. The measures are intended to coerce the Sudanese government's acceptance of a 23,000-strong African Union and United Nations peacekeeping force for Darfur. But in the absence of a viable peace process there are serious limitations to what the force could achieve. Indeed, the recent focus on intervention in Darfur obscures the larger issues at stake. Foremost among these is the North-South peace process and its centrepiece, the Comprehensive Peace Agreement (CPA). There is real risk that the CPA could collapse, and along with it, the best chance for a durable settlement to Sudan's wars.(SWP Comments / SWP)
Keywords: 320